PHYTOCHEMICAL SCREENING AND ANALYSIS POLYPHENOLIC ANTIOXIDANT ACTIVITY OF METHANOLIC EXTRACT OF WHITE DRAGON FRUIT (Hylocereus undatus) - VH, Elfi Susanti; Utomo, Suryadi Budi; Syukri, Yandi; Redjeki, Tri (Indonesian Journal of Pharmacy, 2012)
White dragon fruit  is  a well  known  and  widely  used  herbal medicine,  especially  in  Asia,  which  contains  several  interesting bioactive constituents and possesses health promoting properties. The  aim  of  this  study  was  to  analyze  for  the  bioactive compounds,  evaluate  total  phenolic  contents  and  antioxidant capacities  of  methanolic  extract  of  white  dragon  fruit.  The antioxidant  activity  was  determined  by  the  1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity assay. Total phenolic  content  were  determined  by  Folin-Ciocalteu  method. Phytochemical  screening  of  the  white  dragon  fruit  showed the  presence  of  triterpenoid,  alkaloid,  flavonoid  and  saponin. The  extract  exhibited  strong  antioxidant  activity  with  IC50 of 193 μg/mL, and total phenolic content of 246 μg/mL in 1 Kg dry extract.Key words: antioxidant activity, total phenolic, DPPH, white dragon fruit